Pengaruh Kinerja Keuangan dan Regulasi e-IPO terhadap Underpricing Saham IPO di Bursa Efek Indonesia - Maynisa Naomi Marpaung; Christella Miranda Josephine Simbolon; Solagratia Raya Manalu; Putri Kemala Dewi Lubis (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
This study aims to examine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), and e-IPO regulation on the level of IPO underpricing on the Indonesia Stock Exchange during the 2021–2025 period. The research employs a causal quantitative approach using multiple linear regression analysis. Secondary data were collected from the prospectuses and financial statements of companies conducting Initial Public Offerings (IPOs).The results indicate that ROA does not have a significant effect on underpricing (significance value = 0.181). Similarly, DER is found to have no significant influence on underpricing (significance value = 0.268). The simultaneous test also shows a non-significant result, with an F-significance value of 0.120, suggesting that the independent variables collectively do not affect IPO underpricing. Furthermore, the coefficient of determination (R²) of 0.175 implies that only 17.5% of the variation in underpricing can be explained by the variables included in the model, while the remaining 82.5% is attributable to other factors outside the study, such as market sentiment, underwriter reputation, and oversubscription levels. These findings suggest that investors in the Indonesian IPO market tend to prioritize short-term capital gain opportunities rather than relying on firms’ financial fundamentals. Consequently, accounting-based indicators are not sufficiently influential in shaping stock prices during the first day of trading.